Problems Encountered by English Teachers During the Onsite Transitional Period in SMA Negeri 1 Bangli - Putu Agung Wawan Widyasastrena (STKIP AGAMA HINDU SINGARAJA, 2023)
With the decline in COVID-19 cases in Indonesia, the government devised a strategy to permit students to resume attending school and engage in face-to-face learning. Consequently, teachers had to make necessary adjustments to their teaching approaches in order to accommodate this onsite learning transitional phase. These adjustments create new problems that teachers need to be encountered. This study aims to identify problems encountered by English teachers at SMA Negeri 1 Bangli. This study conducted in qualitative method. The data collected by interview through structured interview guide. The findings showed that teachers encountered various problems such as poor internet connectivity when conducting online quizzes, students cheating in a test, and some problems with parents who dissatisfied with the students’ learning result.